One-Pot Microwave-Assisted Synthesis of 2,4-Dichloroquinolines - (Arman) Taherpour, Avat; Kheradm, Khojasteh; Rostami, Behroz; Abdotajedini, Ehtesham; Rashno, Vahid (Asian Journal of Chemistry, 2010)
In this paper, a fast one-pot microwave-assisted conversion of aromatic amines to 2,4-dichloroquinolines in presence of POCl3, malonic acid (CH2(COOH)2) and under microwave irradiation (600 W, 50 s) in good yields was reported. The products were characterized by FT-IR, GC/MS and NMR spectroscopy results.